Other-serving double standards: People show moral hypercrisy in close relationships. (November 2021) - Weiss, Alexa; Burgmer, Pascal
Extending research on self-serving double moral standards (hypocrisy), we examine the reverse pattern of other-serving hypercrisy toward close relationship partners. In three studies ( N = 1, 019), for various imagined transgressions, people made more lenient moral judgments for their close friends (Studies 1 & 2) and romantic partners (Study 3) compared to themselves. This hypercrisy effect emerged both for transgressions toward third parties (Study 1) and toward each other (i.e., within the relationship; Studies 2 & 3). Moreover, it was moderated by perceptions of the relationship: Participants who more strongly believed their relationship to be a zero-sum game (i.e., needs can only be met competitively) showed greater leniency for themselves and attenuated hypercrisy for mutual transgressions (Studies 2 & 3). Investigating people's close others rather than strangers as targets of moral judgment thus suggests that other-serving hypercrisy is more prevalent than previously thought, but sensitive to people's conceptualizations of their relationships.